Thallium uptake by white mustard (Sinapis alba L.) grown on moderately contaminated soils--agro-environmental implications - Vanek, Ales; Komárek, Michael; Chrastný, Vladislav; Becka, David; Mihaljevic, Martin; Sebek, Ondrej; Panusková, Gabriela; Schusterová, Zuzana (Journal of hazardous materials, 2010)
The work focused on Tl uptake by white mustard (Sinapis alba L.) grown on moderately contaminated soils with different characteristics. The data presented here clearly demonstrate the ability of white mustard to (hyper)accumulate Tl. Substantially higher Tl levels were was found in mustard grown on the Arenosol as compared to the carbonate-rich Leptosol; a relationship between the content of labile Tl (adsorbed, bound to carbonates etc.) in soil and its uptake by the plant is suggested. Approximately 3-fold lower concentrations of Tl in roots and stems of the mature mustard (compared to the young plant) indicate a decreasing trend of Tl uptake with the age of the plant. The exchangeable/acid-extractable and reducible Tl fractions were evaluated as the dominant fractions controlling Tl transfer from both contrasting soils. Thallium associated with the residual fraction (e.g., incorporated into silicates) was rather stable in the rhizosphere, proving a negligible influence of root exudates on Tl release from such an operationally defined fraction, despite the anthropogenic origin of Tl. Regarding our results, when mustard is cultivated for nutrition purposes and/or as green manure, it may pose an important source of Tl introduction into the food chain.
Keywords: látky znečišťující půdu; Brassicaceae; Soil Pollutants; řízení kvality; Thallium; thallium; Quality Control